345 Phase 3 study of combination pembrolizumab + olaparib therapy versus enzalutamide/abiraterone in metastatic castration-resistant prostate cancer (mCRPC) after progression on chemotherapy (KEYLYNK-010). (9th November 2020) - Yu, Evan; Park, Se Hoon; Huang, Yi-Hsiu; Bennamoun, Mostefa; Xu, Lu; Kim, Jeri; Antonarakis, Emmanuel
Abstract : Background: Cohort A of the phase 1b/2 KEYNOTE-365 study (NCT02861573 ) demonstrated promising antitumor activity with pembrolizumab + olaparib in patients with mCRPC unselected for homologous recombination deficiency. The prostate-specific antigen (PSA) and objective response rates (ORR) were both 9%, progression-free survival (PFS) was 4.3 months, overall survival (OS) was 14.4 months, and 12-month PFS and OS rates were 23.3% and 58.2%, respectively. The safety profile of the combination therapy was also aligned with the individual profiles of each agent. KEYLYNK-010 (NCT03834519 ) is a phase 3 trial to evaluate efficacy and safety of pembrolizumab + olaparib in molecularly unselected enzalutamide- or abiraterone-pretreated patients with mCRPC who progressed with docetaxel chemotherapy. Methods: Eligibility criteria include histologically confirmed mCRPC unselected for homologous recombination repair (HRR) gene mutation, progression on docetaxel chemotherapy, progression on androgen deprivation therapy within 6 months before screening, received either abiraterone for metastatic castration-sensitive prostate cancer/mCRPC or enzalutamide for mCRPC (but not both) for ≥8 weeks (≥14 weeks with bone progression), and Eastern Cooperative Oncology Group performance status of 0 or 1. Patients will also be required to provide tumor tissue for biomarker analysis. Approximately 780 adults will be randomized in a 2:1 ratio to pembrolizumab 200 mg IV Q3W (maximum 35 cycles) + olaparib 300 mg PO QD or abiraterone 1000 mg PO QD + prednisone or prednisolone 5 mg PO BID (enzalutamide-pretreated patients) or enzalutamide 160 mg PO QD (abiraterone-pretreated patients). Randomization will be stratified by prior treatment (abiraterone or enzalutamide) and measurable disease (yes/no). Treatment for all patients will continue until disease progression, unacceptable toxicity, or withdrawal. Response will be assessed by imaging (CT/MRI/bone) per Prostate Cancer Working Group 3 (PCWG3)–modified RECIST v1.1 by blinded independent central review (BICR) Q9W during the first year and then Q12W thereafter. The dual primary end points are radiographic PFS per PCWG3-modified RECIST v1.1, as assessed by BICR and OS. The key secondary end point is time to initiation of subsequent anticancer therapy or death. Other secondary end points include ORR, duration of response, time to PSA progression, time to first symptomatic skeletal-related event, and safety and tolerability. Patient-reported outcomes and identification of molecular biomarkers for treatment response are exploratory end points. KEYLYNK-010 is ongoing or planned in 19 countries across Asia, Australia, Europe, and North and South America. Results: N/A Conclusions: N/A Trial Registration: ClinicalTrials. gov, NCT03834519 Ethics Approval: The study and the protocol were approved by the Institutional Review Board or ethics committee at each site.